The school hygiene textbooks for teachers in Cuba, 1902-1963 - Cordoví, Yoel (Historia y Memoria de la Educación, 2018)
This article analyzes the contents of the school hygiene textbooks for teachers, from the publication of the first Manual or guide for the examinations of Cuban teachers, in 1902 - the date of the establishment of the Republic of Cuba -, up until the edition of the Basic Fundamentals of Hygiene Escolar, in 1963, after the nationalization of education that came with the triumph of the Cuban Revolution. Rather than attempting to describe each of the ten textbooks studied, our main objective is to identify trends showing continuity as well as changes in content and hygienic-pedagogical approaches. The structure of the text responds essentially to methodological conceptions for the analysis of the publishing world as related to the specialized manuals in Cuba. In particular, the public (political) «uses» of school hygiene in pedagogical discourses are analyzed, according to the rhetoric of Cuban nationalism in different contexts, as well as its incidence in the changes of denomination and curricular orientation that mediate between the conception of the subject Physiology and Hygiene (1902-1944) and that of Education for Health (1944-1963).